Pemberdayaan Perempuan melalui Simpan Pinjam di Nagari Talang Kecamatan Gunung Talang Kabupaten Solok - Redni Putri Meldianto; Silfia Hanani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Empowerment of women through savings and loans is a potential to overcome women's poverty, to increase women's income, assistance is provided through savings and loans. Women's savings and loan activities are in line with the development priorities Sustainable Development Goals , namely overcoming poverty and reducing inequality. The gender analysis used in this article is GAD (Gender And Development).To analyze women's empowerment through savings and loan activities, this article uses qualitative data. Women are a category of society who are economically marginalized, therefore women are considered as individuals. The purpose of this article is to understand the process of empowering women through savings and loans for business capital in Nagari Talang, Gunung Talang District, Solok Regency. Savings and loans for business capital are aimed at women who have businesses, members can develop their own businesses